DETERMINATION OF TOTAL WATER CONSUMPTION AND WATER CONSUMPTION COEFFICIENT WHEN IRRIGATED WITH WASTEWATER IN THE GROWING OF CORN (SILAGE) CROP. (Proceedings of International Educators Conference, 2023)
Efficient use of water resources in irrigated agriculture is one of today's global problems. In the territory of Uzbekistan, 12-14 thousand m3 of water is used to cultivate 1 hectare of land. [2] In our conducted scientific research work, the cultivation of corn (for silage) crops in wastewater as feed for livestock has been achieved and positive results have been achieved. When the water consumption of corn is 70-70% compared to limited field moisture capacity in the first irrigation (in 2020) regime (in irrigation with fertilizer and wastewater) 2723 m3/ha, productivity - 416 ts/ha and water consumption coefficient 8.2 m3/s*ha , in option 4 (irrigation with wastewater) when irrigation was 70-80% compared to limited field moisture capacity, water consumption was 2814 m3/ha, productivity was 432 tons/ha, water consumption coefficient was 8.0 m3/s*ha.